2019
DOI: 10.1111/bjir.12504
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Computer Use on Work Discretion and Work Intensity: Evidence from Europe

Abstract: This article studies changes in computer use and work discretion and intensity in the EU-15 between 1995 and 2015. We document that while the proportion of workers using computers has increased from 40 per cent to more than 60 per cent, there remain significant differences between countries even within the same occupations. Several countries have seen a significant increase in computer use even in low-skilled occupations generally assumed to be less affected by technology. Overall, the great increase in comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 63 publications
2
34
1
1
Order By: Relevance
“…The large majority of British workers (89% in 2017) make some use of computers or automated equipment in their jobs. Our finding contrasts with that of Menon et al (2019), who reported insignificant computer effects on work intensity except for among routine cognitive occupations. This difference may have arisen from both methodological and data differences, including that their study combines two dichotomous indicators to measure work intensity, uses a dichotomous indicator of computer use, and focuses on Europe as a whole.…”
Section: Discussion: What Accounts For Persistent Generic Workcontrasting
confidence: 99%
See 1 more Smart Citation
“…The large majority of British workers (89% in 2017) make some use of computers or automated equipment in their jobs. Our finding contrasts with that of Menon et al (2019), who reported insignificant computer effects on work intensity except for among routine cognitive occupations. This difference may have arisen from both methodological and data differences, including that their study combines two dichotomous indicators to measure work intensity, uses a dichotomous indicator of computer use, and focuses on Europe as a whole.…”
Section: Discussion: What Accounts For Persistent Generic Workcontrasting
confidence: 99%
“…Bittman, Brown, and Wajcman (2009) found that mobile phones at work intensified the work of men, though not of women, in a sample of Australian workers. By contrast, Menon, Salvatori, and Zwysen (2019) found only small effects in a pan-European Union study. Taken together, these studies do not establish that growing ICT use alone has a large enough effect to explain the observed widespread extent of work intensification.…”
Section: Work Intensity and Work Intensificationmentioning
confidence: 80%
“…In other words, the increase in robots between 1995 and 2005 from .8 2.1 per thousand workers led to an increase in work intensity of 5.6 7.3 points (87 114 percent of a standard deviation in 2000). These eects are rather large, but comparable to those of Menon et al (2019) in size: They calculate the eect of computers on working conditions in the European Union; they nd negative but insignicant coecients for the impact of computer use on work intensity, but a positive impact of computer use on work quality in terms of work discretion.…”
Section: Resultsmentioning
confidence: 92%
“…-Macías et al[2015],Green et al [2013],Menon et al [2019], and Muñoz deBustillo et al, 2011). We formulate indicators in such a way, that all questions are available in the three waves of the survey.The index of quality of work intensity comprises two sub-dimensions, quantitative demands and pace determinants and interdependency.…”
mentioning
confidence: 99%
“…Starting with the early work of Braverman (1974), socio-economic research has suggested that technologies lead to higher monitoring, lower skill requirements, and more precise tasks specification, and especially so for lower-skilled workers whose tasks do not require expert knowledge and creative thinking (Hunter & Lafkas, 2003;Menon et al, 2019). The growth in usage of ICT technologies since the 1970s has had the potential to reduce the autonomy and control over the work process of lower-level employees, therefore tempering their wage growth.…”
Section: Technological Changementioning
confidence: 99%